Kajian Efektivitas Program Rehabilitasi sebagai Salah Satu Sektor Rencana Kerja Asean dalam Menangani Anak Penyalahguna Narkotika - Ahmad Fajar Satrio (HUMANIORUM, 2023)
Currently, drug abuse by children continues to be a public concern and never stops being discussed and publicized. Certain circles, such as ASEAN (the Association of Southeast Asian Nations), have always been committed to fighting the threat of drugs in the Southeast Asian region. The main vision of the region is to achieve a "drug-free ASEAN". Referring to the vision and slogan, ASEAN formed an ASEAN Work Plan (ASEAN Work Plan) with one sector, namely rehabilitation. The purpose of this research and study in general is to find out and discuss the effectiveness of the rehabilitation program as a sector of the ASEAN work plan in dealing with children who abuse narcotics. The method used for writing this journal is a normative legal method using a quantitative and qualitative approach. In writing this journal, the authors also follow a research typology that is descriptive in nature. Based on the research results, it can be concluded that the rehabilitation program, as a sector of the ASEAN work plan, can be said to be somewhat successful in dealing with children who abuse narcotics. However, the data above is not enough to prove that the rehabilitation program is a sector of the ASEAN work plan. This is due to the absence of proportions and data showing the results of the rehabilitation program as a sector of the ASEAN work plan. Referring to the Indonesian Drug Reports, BNN stated in the Mid-Term Review of the ASEAN Work Plan that the proportion of success in the rehabilitation sector was 80%..